"I won't be a guinea pig": Rethinking public health communication and vaccine hesitancy in the context of COVID-19. Issue 1 (4th January 2023) - Michelle Driedger, S.; Capurro, Gabriela; Tustin, Jordan; Jardine, Cindy G.
Abstract: At the beginning of 2021, when Canada started distribution of COVID-19 vaccines, the unprecedented scope and severity of the pandemic led to very high levels of public awareness and attention, with Canadians actively seeking information. We argue that while there was continuous public health communication about COVID-19 and the newly available vaccines, these messages did not address the specific anxieties elicited by the novel vaccines, even as vaccination guidelines changed. Instead, public health messages about COVID-19 vaccines resembled those aimed at reducing vaccine hesitancy for routine immunization and did not sufficiently address the constant changes to COVID-19 vaccine recommendations. In a context of heightened public concern and significant public attention, it is crucial for communicators to acknowledge that hesitancy is vaccine-specific, and that novel diseases and new vaccines produce specific concerns. Long-term strategies should address the novelty of the technology and of the risk, thoroughly explain the reasons for shifting vaccination guidelines, and leverage trusted sources, such as community leaders. Further, as COVID-19 vaccines become less effective against some of the more recent variants of the virus, vaccine messaging needs to be tailored to evolve with shifting realities to not lose productive gains in the COVID-19 vaccination campaign to date.